ANALISIS PENGARUH PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BESI PUTIH DI KOTA AMBON (studi empiris pada Toko Besi Putih Asli (Khas) Maluku Di Kota Ambon) - Merry M Pelupessy (Soso-Q : Jurnal Manajemen, 2018)
This study aims to examine the influence of Promotion and Price Influence on Iron Iron Purchase Decision In Ambon City (Empirical Study On The Original White Iron Store (Typical) Maluku In Ambon City) ". Population in this research is Population in this research is consumer of Original White Iron Store (Typical) Maluku In Ambon City. Sampling technique using purposive sampling with sample of 100 people. While the analysis technique used is multiple linear regression. Promotion Variables based on the test results showed significant influence to the purchase decision of 4.953 with a significance of 0.000. Variable Price based on the test results showed a significant influence on the Purchase Decision of 4.680 with a significance of 0.000. From the results of statistical tests of Promotion and Price variables to purchase decisions, it is known that Promotion variables have a greater influence on purchasing decisions that amounted to 4.953 with a significance of 0.000, compared to the variable price of 4.680 with a significance value of0.000.Keywords: Promotion, Price and Purchase Decision